2015
DOI: 10.1007/s12035-015-9414-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Ubiquitination by Paraquat and 1-Methyl-4-Phenylpyridinium Impairs Ubiquitin-Dependent Protein Degradation Pathways

Abstract: Intracytoplasmic inclusions of protein aggregates in dopaminergic cells (Lewy bodies) are the pathological hallmark of Parkinson’s disease (PD). Ubiquitin (Ub), alpha [α]-synuclein, p62/sequestosome 1 and oxidized proteins are major components of Lewy bodies. However, the mechanisms involved in the impairment of misfolded/oxidized protein degradation pathways in PD are still unclear. PD is linked to mitochondrial dysfunction and environmental pesticide exposure. In this work, we evaluated the effect of the pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 183 publications
(234 reference statements)
0
12
0
1
Order By: Relevance
“…Paraquat and 1-methyl-4-phenylpyridinium (MPP+) are environmental toxicants associated with an increased risk of developing Parkinson’s disease, a neurodegenerative pathology characterized by an accumulation of insoluble protein deposits. Exposure of dopaminergic cells to paraquat or MPP+ was shown to decrease protein ubiquitination, leading to a dysfunction of protein degradation pathways 36 . The molecular target of radicicol is the heat-shock protein Hsp90p, the inhibition of which affects protein quality control 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat and 1-methyl-4-phenylpyridinium (MPP+) are environmental toxicants associated with an increased risk of developing Parkinson’s disease, a neurodegenerative pathology characterized by an accumulation of insoluble protein deposits. Exposure of dopaminergic cells to paraquat or MPP+ was shown to decrease protein ubiquitination, leading to a dysfunction of protein degradation pathways 36 . The molecular target of radicicol is the heat-shock protein Hsp90p, the inhibition of which affects protein quality control 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that PQ may, at least to some extent, impair the protein ubiquitination pathway. Previous studies also reported that PQ can induce ubiquitin/proteasome system dysfunction (Navarro-Yepes et al 2016;Yang et al 2007).…”
Section: Ubi4 Deficiency Induces Early Apoptosis In Yeastmentioning
confidence: 74%
“…The extent of protein oxidation in the hippocampus was assessed by measuring the content of protein carbonyl groups, using 2,4-dinitrophenylhydrazine (DNPH) derivatization as described by Oliver et al [38] and following the indications of Luo and Wehr [39, 40]. Basically, the supernatant fraction was divided into two equal aliquots containing approximately 2 mg of protein each.…”
Section: Methodsmentioning
confidence: 99%